2020
DOI: 10.3390/ijms21228584
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of GPx-3 in the Reciprocal Control of Redox Metabolism in the Leukemic Niche

Abstract: The bone marrow (BM) microenvironment plays a crucial role in the development and progression of leukemia (AML). Intracellular reactive oxygen species (ROS) are involved in the regulation of the biology of leukemia-initiating cells, where the antioxidant enzyme GPx-3 could be involved as a determinant of cellular self-renewal. Little is known however about the role of the microenvironment in the control of the oxidative metabolism of AML cells. In the present study, a coculture model of BM mesenchymal stromal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…AML cells are known to exhibit high levels of ROS 52,53 . However, our data has shown that AML cells in co-culture present lower levels of ROS than AML cells cultured alone, which is in agreement with recent studies in primary AML and mesenchymal stromal cell co-cultures 14,24 . The current mechanisms to describe this phenomenon involve mitochondrial transfer and activation of glutathione-related antioxidant pathways 14,24 , although previous data on haematopoietic stem cells (HSCs) revealed that HSCs can directly transfer ROS via gap junctions to stromal cells 32 .…”
Section: Studying the Interactions Between Cancer Cells And Their Microenvironment In Terms Of Metabolismsupporting
confidence: 93%
See 1 more Smart Citation
“…AML cells are known to exhibit high levels of ROS 52,53 . However, our data has shown that AML cells in co-culture present lower levels of ROS than AML cells cultured alone, which is in agreement with recent studies in primary AML and mesenchymal stromal cell co-cultures 14,24 . The current mechanisms to describe this phenomenon involve mitochondrial transfer and activation of glutathione-related antioxidant pathways 14,24 , although previous data on haematopoietic stem cells (HSCs) revealed that HSCs can directly transfer ROS via gap junctions to stromal cells 32 .…”
Section: Studying the Interactions Between Cancer Cells And Their Microenvironment In Terms Of Metabolismsupporting
confidence: 93%
“…For instance, it was reported that Nestin+ bone marrow mesenchymal stem cells (BMSCs) support AML progression by increasing the bioenergetic capacity of AML cells and providing them with glutathione (GSH)-mediated antioxidant defence to balance the excess ROS [14]. Similarly, a recent study showed that co-culturing BMSCs with AML cells leads to a decrease in AML ROS levels due to an activation of the antioxidant enzyme GPx-3 in AML cells [24].…”
Section: Introductionmentioning
confidence: 99%
“…In leukemic cells, the presence of BM-MSCs promotes the overexpression of GPX3, the cytoplasmic relocalization of Nrf2, and inactivation of p38MAPK with a concomitantly decrease in ROS levels. Of note, a reverse effect was observed in BM-MSCs in contact with leukemic cells, with a particular rise in ROS levels, decrease in GPX3 expression, and nuclear relocalization of Nrf2 [ 118 ]. One explanation could be ascribable to a mechanism of ROS transfer between AML cells and MSCs mediated by Connexin(CX)-43, a gap junction protein [ 119 ].…”
Section: The Stromal-dependent Metabolic Reprogrammingmentioning
confidence: 99%
“…Leukemia initiating cells (LICs) interact with their surrounding bone marrow microenvironment ( 22 ), and the complex cell network surrounding LICs determines their fate ( 23 ). Various cellular signaling pathways and metabolic mechanisms regulate the BMMNC microenvironment and contribute to AML development ( 24 , 25 ). However, the detailed regulation mechanism for BMMNC malignant transformation has not been clearly defined.…”
Section: Discussionmentioning
confidence: 99%